Ecotoxicological effects of swine manure on Folsomia candida in subtropical soils - SEGAT,JULIA C. (2020)
Abstract The production model used in Brazilian pig farms promotes a concentration of animals in small territorial extensions, causing difficulty in disposing of the manure generated, since the economically viable alternative is to use this as an agricultural fertilizer. The objective was to evaluate the effect of swine manure doses on the biological and behavioral parameters in Folsomia candida by ecotoxicological tests. An Ultisol, Oxisol and Tropical Artificial Soil (TAS) were contaminated with 0, 25, 50, 75 and 100 m3 ha-1 of swine manure, to which springtails were exposed for evaluation of mortality, and the doses 0, 10, 15, 20 and 25 m3 ha-1 of swine manure to evaluated reproduction and avoidance. Lethality was observed in all doses as well as all soils, indicating toxicity of the manure. In the reproduction tests dose since 10 m3 ha-1 caused a reduction of juveniles in all soils. Avoidance behavior was observed in all doses of the Oxisol treatments and at 20 and 25 m3 ha-1 in Ultisol treatments. However, in TAS occurred not avoidance response of F. candida. We conclude that the swine manure was toxic to F. candida and the toxicity is dependent on the soil characteristics and the manure concentrations applied.